Design and implementation of a high-efficiency low-voltage synchronous reluctance motor - Boztas, Gullu; Aydogmus, Omur; Guldemir, Hanifi (Springer, 2022)
This paper presents a motor design which can operate directly with a low-voltage output photovoltaic panels or batteries. A high-efficiency synchronous reluctance motor which can operate directly at low voltage level without a boost converter was designed in this study. The motor was optimized for maximum torque and minimum torque ripple by using the multi-objective genetic algorithm. A robust, durable and low-cost motor structure was obtained due to the obtained rotor structure. The optimized motor can generate less than 5% torque ripple with rated torque of 2 Nm. The prototype motor efficiency was obtained as 81.2% in experimental study, while the motor efficiency designed was obtained as 87.9% in theoretical study. For this reason, the designed motor was suitable for the IE5 efficiency class. However, the experimentally produced prototype motor was obtained in the IE4 efficiency class. In addition, the motor drive and control algorithm were developed for the designed motor. The details were analyzed for different load conditions in both simulation and experimental environments.
Keywords: Electric motor design; Efficiency; Motor drive; Synchronous reluctance motor